Interpreting broad emission-line variations – II. Tensions between luminosity, characteristic size, and responsivity. Issue 4 (9th September 2015) - Goad, M. R.; Korista, K. T.
Abstract: We investigate the variability behaviour of the broad H β emission-line to driving continuum variations in the best-studied AGN NGC 5548. For a particular choice of broad emission-line region (BLR) geometry, H β surface emissivity based on photoionization models, and using a scaled version of the 13-yr optical continuum light-curve as a proxy for the driving ionizing continuum, we explore several key factors that determine the broad emission-line luminosity L, characteristic size R RW, and variability amplitude (i.e. responsivity) η, as well as the interplay between them. For fixed boundary models which extend as far as the hot dust the predicted delays for H β are on average too long. However, the predicted variability amplitude of H β provides a remarkably good match to observations except during low-continuum states. We suggest that the continuum flux variations which drive the redistribution in H β surface emissivity F ( r ) do not on their own lead to large enough changes in R RW or ηeff . We thus investigate dust-bounded BLRs for which the location of the effective outer boundary is modulated by the continuum level and the dust-sublimation and dust-condensation time-scales. We find that in order to match the observed variability amplitude of broad H β in NGC 5548 a rather static outer boundary is preferred. Intriguingly, we show that the most effective way of reducing the H β delay, while preserving its responsivity and equivalent width, is to invoke a smaller value in the incident ionizing photon flux ΦH for a given ionizing source–cloud radial distance r, than is normally inferred from the observed UV continuum flux and typical models of the continuum spectral energy distribution.